2017
DOI: 10.1177/0960327117712386
|View full text |Cite
|
Sign up to set email alerts
|

Acrylamide-derived cytotoxic, anti-proliferative, and apoptotic effects on A549 cells

Abstract: Our research suggests that acrylamide causes cytotoxic, anti-proliferative, and apoptotic effects on A549 cells at 4.6 mM IC dose in 24 h.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 30 publications
0
24
0
1
Order By: Relevance
“…Similar to our results, Mehri et al (2012) performed annexin V tests for acrylamide-treated PC-12 cells and found that acrylamide increased early, late, and total apoptotic cells. Moreover, Kacar et al (2017) detected a 5.25-fold increase in late apoptotic and a 2.87-fold increase in the total apoptotic rate of acrylamide-treated A549 cells by the annexin V test.…”
Section: Discussionmentioning
confidence: 86%
“…Similar to our results, Mehri et al (2012) performed annexin V tests for acrylamide-treated PC-12 cells and found that acrylamide increased early, late, and total apoptotic cells. Moreover, Kacar et al (2017) detected a 5.25-fold increase in late apoptotic and a 2.87-fold increase in the total apoptotic rate of acrylamide-treated A549 cells by the annexin V test.…”
Section: Discussionmentioning
confidence: 86%
“…The International Agency for Research on Cancer (IARC, 1994)AUTHOR: IARC, 1994 has not been included in the Reference List, please supply full publication details. classified AA as ‘a probable human carcinogen’ in Group 2A and its cytotoxicity and antiproliferative properties were confirmed on human cell lines As549 and IC 50 of AA was 4.5 m m (Kacar et al ., ). AA is a by‐product of the Maillard reaction (Stadler & Theurillat, )AUTHOR: Stadler et al ., 2017 has been changed to Stadler and Theurillat, 2017 so that this citation matches the Reference List.…”
Section: Introductionmentioning
confidence: 97%
“…This effect can be attributed to the increase in lipid peroxidation and mitochondrial membrane depolarization associated with oxidative stress (Lee et al 2014). Acrylamide and glycidamide are known to trigger apoptosis in numerous cell lines and various laboratory animal tissues (Yousef & El-Demerdash 2006, Lee et al 2014, Li et al 2017, Kacar et al 2018, Sun et al 2018. In one such study, Li et al (2017) applied glycidamide to R2C Leydig cells at concentrations of 0.635, 0.872 and 1.198 mM, and found, through a Comet test, that glycidamide induced cell apoptosis at an early phase.…”
Section: Discussionmentioning
confidence: 99%
“…In one such study, Li et al (2017) applied glycidamide to R2C Leydig cells at concentrations of 0.635, 0.872 and 1.198 mM, and found, through a Comet test, that glycidamide induced cell apoptosis at an early phase. In a study performed on A549 human lung adenocarcinoma cell line, the ratio of apoptosis in cells exposed to 4.6 mM concentrations of acrylamide was reported as 64 percent (Kacar et al 2018). Chen et al (2013) found that acrylamide at 1 and 2 mM concentrations caused structural changes in the mitochondria of astrocytoma cells, along with mitochondria-dependent apoptosis.…”
Section: Discussionmentioning
confidence: 99%